Envelhecer longe de casa: aspectos culturais e sociais de refugiados na cidade de São Paulo - Collus, Denise Orlandi (2015)
The objective of this research work was to identify and analyze the variables that contributed to the adaptation to the aging process by refugees aged over 55 years in the city of São Paulo. A review of the literature on refugees and aging was undertaken to assist in understanding the issue selected for study: aging away from home: refuge and old age. Based on the oral life history - obtained through open interviews - of nine refugees from different nationalities, some variables were identified that were similar among the interviewees regarding life experience and/ or expectations about aging. Among the variables that may increase the likelihood of successful aging are autonomy, mastery of the host country s language, religious beliefs, hospitality, family and freedom. However, three other features can hinder adaptation to old age: financial dependency, disease and family vulnerability. The result of the research supports this assertion, and reveals these refugees extraordinary capacity to overcome challenges, which derives perhaps from the abilities they were forced to develop throughout their lives marked by challenges and achievements